Characterization of novel high-speed die attachment method at 225 °C using submicrometer Ag-coated Cu particles. (June 2018) - Lee, Chang Hyun; Choi, Eun Byeol; Lee, Jong-Hyun
Abstract: A novel die-attaching technology, using the in-situ dewetting of Ag shells in submicrometer Ag-coated Cu (Cu@Ag) particles during heating in air, was suggested for power device packaging. The particle size-dependent dewetting of Ag induced the formation of tiny nodules and rapid sinter bonding via fast Ag transfer under external pressure. A die attached by thermal compression for 5 min at 225 °C using 200- or 350-nm Cu@Ag particles showed shear strengths approaching or surpassing that (18.0 MPa) of a die attached using Pb-5Sb. Graphical abstract: Unlabelled Image